Analysis of influence factors of methane adsorption capacity of the Lower Silurian shale. (17th December 2018) - Sun, Yaxiong; Ding, Wenlong; Lu, Lin; Li, Mingzhu; Chen, Peng; Ji, Xiang
Abstract: The Lower Silurian marine shale gas in South China has great potential. In order to study the influence factors of methane adsorption capacity of the marine shale in Sangzhi block, six samples from the Lower Silurian were investigated by a series of experiments. The total organic carbon (TOC) content ranges from 1.97 to 3.49% and organic matter are in the state of over-maturity. The dominant mineralogical compositions are quartz and clay minerals. The methane adsorption capacity of the studied shale ranges from 1.5627 to 2.2033 cm 3 /g, and is mainly influenced by the TOC content.